Internalizing Character Education and Moral Values through 3S Habituation (Smile, Greeting, and Salutation) in Early Childhood Education - Azzura Permata Sari; Dwi Istiyani; Muslam (Program Studi Pendidikan Guru Pendidikan Anak Usia Dini, Fakultas Ilmu Pendidikan, Universitas Negeri Makassar, 2025)
This study aims to explore the internalization of character education and moral values through the implementation of the 3S habituation program (Smile, Greeting, and Salutation) in early childhood education. The problem addressed in this study concerns the need for effective habituation-based strategies to develop politeness, empathy, respect, and courteous communication among early childhood learners. The research employed a descriptive qualitative approach. The researcher served as the primary instrument in collecting and interpreting data. The study was conducted at KB–TK Al Azhar 29, Semarang. Data sources consisted of teachers, school administrators, children, and supporting documents. Data were collected through observation, interviews, and documentation. The findings reveal that the 3S habituation program has been integrated into all daily activities, including morning greetings, learning processes, transition activities, and dismissal time. Teachers play a pivotal role as role models by consistently demonstrating positive behavior and providing positive reinforcement. As a result, children showed improvements in polite verbal interactions, basic conflict resolution skills, and social sensitivity. These findings indicate that consistent 3S habituation serves as an effective strategy for internalizing character education and moral values in early childhood education settings.